The Application of Educational Planning Principles in MI/SD - Abdul Latif Hutagaol; Fachruddin Azmi; Mesiono Mesiono; Muhammad Isa; Azhar Azhar (Jurnal Basicedu, 2022)
This study aims to describe the application of Islamic education planning principles in MI/SD. The background of this research is located at MIS Qur'an Kisaran Jalan Jahe, Environment IV Sentang Village, Kota Kisaran Timur District, Asahan Regency. This study uses a qualitative approach with a descriptive method. Obtaining data using observation techniques in the form of observing managerial activities in the madrasa, interviews with informants including the head of the madrasa and deputy head of the madrasa, as well as document studies to strengthen the completeness of the validity of the data relevant to the research theme. The data analysis of this research uses data reduction (sorting) techniques, data presentation, to verification and drawing conclusions. The results of this study concluded that educational planning at MIS Qur'an Kisaran was carried out well according to the principles of educational planning. This is indicated by the implementation of annual meetings that formulate educational concepts and programs for the allocation of budget funds for certain period activities (madrasah program planning team), procurement of learning facilities (by presenting the head of the Ministry of Religion of the Asahan Regency), and establishing internal madrasa policies through collaboration with agencies or institutions. related institutions.